2019
DOI: 10.1177/1757913919834584
|View full text |Cite
|
Sign up to set email alerts
|

NHS Health Check and healthy lifestyle in Leicester, England: analysis of a survey dataset

Abstract: Aims: A major component of the National Health Service (NHS) Health Check in England is to provide lifestyle advice to eligible participants. The aims of the study were to explore the variations (in terms of uptake) in the NHS Health Check in Leicester and to determine its association with a healthy lifestyle. Methods: This cross-sectional study used data from the Leicester Health and Wellbeing Survey (2015). Results: The odds of having an NHS Health Check were found to be higher in Black and minority ethnic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…22 There is evidence to suggest lower levels of NHS-HC attendance among smokers. 20 21 One study 20 Open access no religious background were less likely to attend overall. This finding was from a single small community-based study and it is, therefore, difficult to make any inferences about the wider population.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…22 There is evidence to suggest lower levels of NHS-HC attendance among smokers. 20 21 One study 20 Open access no religious background were less likely to attend overall. This finding was from a single small community-based study and it is, therefore, difficult to make any inferences about the wider population.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, more older adults (eg, >60 years old) attended than younger adults. [18][19][20] Evidence suggested men are less likely to attend than women, 17-19 21 22 as statistically evidenced in 21 (adjusted OR (AOR): 0.75, 95% CI: 0.67 to 0.84) and 19 (AOR: 0.73, 95% CI: 0.67 to 0.8). Another study 20 however, provide some evidence that men may be more likely to attend than women when the NHS-HCs were conducted opportunistically, where health checks are offered to patients during face-to-face medical consultations for other reasons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is strong evidence for each of the risk management options individually, the introduction of the programme has not been without controversy, 6 8 and the benefits of the programme have been smaller than in early modelling. 9 13 Alongside an increasing focus on prevention generally, however, both the NHS Long Term Plan 14 and prevention ‘green paper’, published in July 2019, 15 cite the importance of NHS Health Checks in the future. Understanding how well the programme is currently being delivered, and whether it is being delivered as intended (that is, the ‘fidelity’), 16 is therefore important.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study in Leicester showed variation in uptake between socioeconomic and demographic groups and no association with adopting a healthy lifestyle. 3 The pressure on clinicians to mediate behaviour as well as to treat the results of poor lifestyle may contribute to the high prevalence of stress in doctors – Locke and Lees identify that a review of the evidence base for interventions provides a useful summary of successful approaches, with the need for interventions to be tailored to particular specialties and contexts. 4 Pharmacists also play an important part in advising the public, and integrated pharmacy curricula are helping to ensure they have the appropriate knowledge and skills to do so.…”
mentioning
confidence: 99%